Meralgia Paresthetica after Prone Positioning Ventilation in the Intensive Care Unit - Christian Svendsen Juhl; Martin Ballegaard; Morten H. Bestle; Peer Tfelt-Hansen (Case Reports in Critical Care)
Meralgia paresthetica (MP) is a mononeuropathy of the lateral femoral cutaneous nerve (LFCN) caused by external compression of the nerve during its course close to the anterior superior iliac spine. We present a case of a patient with acute respiratory distress induced by Legionella pneumonia who was admitted to the intensive care unit (ICU) for mechanical ventilation. In the ICU, the patient received one session of prone position ventilation for 8.5 consecutive hours. At evaluation six months later, the patient reported persistent bilateral numbness of the anterolateral thigh, which he complained had begun right after he woke up at the ICU. He was referred for further neurological and neurophysiological examination and was diagnosed with bilateral MP, a condition never previously described as a complication to mechanical ventilation in prone position in the ICU.